Customer Satisfaction and Behavioral Intentions in Tourism: A Literature Review - Wayan Ardani; Ketut Rahyuda; I Gusti Ayu Ketut Giantari; I Putu Gde Sukaatmadja (International Journal of Applied Business and International Management, 2019)
Purpose: The relationship between customer satisfaction and behavioral intentions in tourism has drawn significant attention for both practitioners and academicians as it is the key factor in winning market share in the tourism industry. The aim of this paper is to present a systematic research of the literature on the topic of customer satisfaction and behavioral intentions in tourism, highlighting the role of both the antecedents and the consequences of satisfaction that have been included in previous research. Methodology: The systematic literature review (SLR) of articles that have been published related to customer satisfaction and behavioral intention in tourism from various journals from 1990 up to 2018. Findings: The result of this study revealed that service quality is the most important antecedents of satisfaction in tourism. Meanwhile, the consequences are mainly characterized by loyalty. Nevertheless, the relationship between customer satisfaction and loyalty does not seem always so linear, as there are customers who revisit to the tourist destination, while others prefer to visit to new destinations despite, they were satisfied Practical implications: It is expected that this study will provide a better understanding of satisfaction towards a tourist destination, so marketing strategy can be composed and implemented in order to increase tourist satisfaction. This article can be as reference for future studies on satisfaction and customer behavioral intentions in tourism.